2019
DOI: 10.1074/jbc.ra119.008762
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal metal transporter ZIP14 maintains systemic manganese homeostasis

Abstract: ZIP14 (encoded by the solute carrier 39 family member 14 [SLC39A14] gene) is a manganese (Mn) transporter that is abundantly expressed in the liver and small intestine. Loss-of-function mutations in SLC39A14 cause severe hypermanganesemia. As the liver is regarded as the main regulatory organ involved in Mn homeostasis, impaired hepatic Mn uptake for subsequent biliary excretion has been proposed as the underlying disease mechanism. However, liver-specific Zip14 knock-out (KO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 52 publications
4
78
0
Order By: Relevance
“…The iron transporters SLC11A2 and SLC40A1 may contribute to this absorption process, however data supporting a critical role are lacking (7)(8)(9)(10)(11)(12)14). In intestinal enterocytes, SLC39A14 at the basolateral membrane and SLC30A10 at the apical membrane limit Mn absorption and/or enhance intestinal Mn excretion (15,16). Once absorbed, Mn is transported to the liver for distribution to other tissues, storage, or use within liver, or excreted from the body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The iron transporters SLC11A2 and SLC40A1 may contribute to this absorption process, however data supporting a critical role are lacking (7)(8)(9)(10)(11)(12)14). In intestinal enterocytes, SLC39A14 at the basolateral membrane and SLC30A10 at the apical membrane limit Mn absorption and/or enhance intestinal Mn excretion (15,16). Once absorbed, Mn is transported to the liver for distribution to other tissues, storage, or use within liver, or excreted from the body.…”
Section: Discussionmentioning
confidence: 99%
“…The metal importer SLC39A14 (also known as ZIP14) and exporter SLC30A10 (also known as ZNT10) have been implicated in Mn transport across the intestines. In cell culture, SLC39A14 mediates basolateral-to-apical/secretory Mn transport, and deficiency in SLC39A14 enhances Mn transport in the apical-to-basolateral/absorptive direction (15). Studies in mice with endoderm-specific Slc30a10 deficiency and mice with intestine-specific Slc39a14 deficiency suggest that intestinal Slc30a10 and Slc39a14 regulate systemic Mn levels (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Divalent Metal Transporter 1 (DMT1, encoded by SLC11A2) transports Mn from the intestinal lumen into enterocytes (31). SLC39A14 takes up Mn from the basolateral side of enterocytes (50), and it has been reported that SLC39A14 acts synergistically with SLC30A10 to mediate whole-body Mn excretion (50)(51)(52). However we found that BA treatments had no effects on Slc11a2 or Slc39a14 expression in murine organoids (Fig.…”
Section: Effects Of Ba Composition On Other Mn Transportersmentioning
confidence: 74%
“…Other hallmarks include iron depletion and hyperbilirubinemia. Mendelian disorders of SLC30A10 and the other hepatic Mn transporter genes SLC39A8 (solute carrier family 39 member 8, causing 56 , along with experiments in transgenic mice57,58 , have confirmed the critical role of each of these genes in maintaining whole-body manganese homeostasis59 . Notably, while all three of the genes have Mendelian syndromes with neurological manifestations, only SLC30A10 deficiency (HMNDYT1) is known to be associated with liver disease 59 .…”
mentioning
confidence: 90%